HADONAH IBU NON-MUSLIM MENURUT AL-NAWAWI DAN ABU ZAHROH PERSPEKTIF SOSIOLOGI PENGETAHUAN - Anam, Muhammad Mufti (Ahkam: Jurnal Hukum Islam, 2019)
ABSTRACTJurisprudence emerges from the dialectic of a faqih and his intellectual social environment. Hadonah by a non-Muslim mother according to al-Nawawi is not permitted because of the reasons for the maslahah and the benefits of Islam over other religions. This jurisprudence is influenced by the background of al-Nawawi who is a hadith scholar and a linguist. While Abu Zahroh tends to allow non-Muslim mothers to breastfeed Muslim children because a mother loves children more than a father, even though there are some exceptions. This thought was due to Abu Zahroh's social and intellectual background who tended to study jurisprudence across schools and studied positive law, philosophy, and non-Islam religion.Keywords: Hadonah, non-Muslim, al nawawi, abuzahroh, sociology of knowledge